EDUCATIONAL SERVICES AS AN ECONOMIC INDICATOR OF SOCIO- ECONOMIC DEVELOPMENT: THE ROLE OF THE HUMAN FACTOR - Mansurova Muzafarra Maksudovna (TADQIQOTLAR, 2026)
Abstract. This article examines educational services as an important economic indicator reflecting the level of a country’s socio-economic development. The economic essence of educational services is revealed, and their impact on the formation of human capital, labor productivity, innovation activity, and the competitiveness of the national economy is analyzed. Particular attention is paid to the role of the human factor in ensuring the effectiveness of educational services. Based on statistical data from the Republic of Uzbekistan, the study considers current trends in the development of the education sector, its contribution to the country’s economy, as well as existing challenges and prospects for the further improvement of educational services in the context of the digital transformation of society.